2011
DOI: 10.1143/jjap.50.080203
|View full text |Cite
|
Sign up to set email alerts
|

Deep-Hole Traps in p-Type GaAs1-xBix Grown by Molecular Beam Epitaxy

Abstract: Deep-level transient spectroscopy measurements reveal deep-hole traps with activation energies of 0.43 and 0.23 eV in p-type GaAs1-x Bi x samples with x = 1.2 and 3.4%, respectively, grown at 370 °C by molecular beam epitaxy. In spite of low-temperature growth, the deep-level trap concentration is suppressed on the order of 1015 cm-3, suggesting that Bi atoms contribute to the enhancement of migration to prevent the formation of point defects. The possi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 19 publications
2
15
0
Order By: Relevance
“…4,5,19 Hole trap concentrations in the 10 15 cm À3 range were previously reported in p-type GaAsBi Schottky diodes having 1.2 and 3.4% Bi (comparable to p-type GaAs grown at 560 C), and it was suggested that this low trap concentration results from incorporating Bi. 20 However, to our knowledge no direct comparison of p-type GaAsBi with p-type GaAs grown at the same temperature has yet been done.…”
Section: Resultsmentioning
confidence: 99%
“…4,5,19 Hole trap concentrations in the 10 15 cm À3 range were previously reported in p-type GaAsBi Schottky diodes having 1.2 and 3.4% Bi (comparable to p-type GaAs grown at 560 C), and it was suggested that this low trap concentration results from incorporating Bi. 20 However, to our knowledge no direct comparison of p-type GaAsBi with p-type GaAs grown at the same temperature has yet been done.…”
Section: Resultsmentioning
confidence: 99%
“…un t) ω−2θ (arc sec) Figure 2a shows the PL spectra of the as-grown and thermally annealed samples at 30 K. The PL signal quenched above 100 K for the as-grown sample and above 200 K for the annealed sample B320. We could not observe any PL signal for the sample B220 even at 30 K. It was reported that a small amount of Bi as a surfactant enhances the structural and optical quality of GaBiAs alloys [14,24,25]. As the growth temperature decreases, even Bi atoms behave as a surfactant, so, a higher nonradiative defect density in GaBiAs, which is grown at very low temperatures, may be expected.…”
Section: Resultsmentioning
confidence: 71%
“…Therefore, it is difficult to observe room temperature PL if the material quality is not good enough. It is well-known that GaBiAs suffer from defects located at around band edges and deep-level traps, resulting in nonradiative transitions and decreased radiative recombination rates [9,[11][12][13][14]. As for measuring defect-assisted PL from a sample, the cross-section of the defect should be high [15].…”
Section: Introductionmentioning
confidence: 99%
“…In our previous DLTS study, we found that by changing the time constant from 1.9 to 31 ms, in spite of the low temperature growth, the deep level trap concentration in the p-GaAs 1Àx Bi x (x < 3:4%) bulk is suppressed on the order of N t , which is given by $10 15 cm À3 , thereby suggesting that Bi atoms contribute to the enhancement of migration in order to prevent the formation of bulk traps. 9) On the basis of the abovementioned results, it was determined that the deep levels measured by TAS are located at the GaAs/p-GaAs 1Àx Bi x heterointerface, rather than in the p-GaAs 1Àx Bi x bulk region. As abovementioned, the interface states density, D it , is evaluated to be approximately 8:8 Â 10 11 cm À2 eV À1 for continuum deep levels and 7:7 Â 10 11 cm À2 eV À1 for single deep levels.…”
Section: Resultsmentioning
confidence: 99%
“…The small trap concentration of $10 15 cm À3 in GaAs 1Àx Bi x was measured by deep-level transient-spectroscopy. 9,10) It was reported that the incorporation of Bi atoms into GaAs induces Bi-related localized states such as Bi clusters to interact with the valence band of GaAs. 11) These Bi-related localized states occur because of the degradation of hole mobility explained by the strong alloy scattering related to localized states.…”
Section: Introductionmentioning
confidence: 99%